Fair Trade Copyright - Helman, Lital (The Columbia Journal of Law & the Arts, 2013)
Digital media has challenged copyright law in the past decades. The ease with which digital files can be copied and disseminated has amplified copyright infringement and jeopardized the profitability of copyright-based industries around the globe. In this article I propose a solution: to complement the copyright system with a Fair Trade Copyright system. The Fair Trade Copyright system, which would apply optimally in the realm of the music industry, would encourage users to donate to recording artists on digital platforms and distribute the donations to artists. The implementation of my proposal will yield several improvements over the current system. First, it would enlarge the pie of revenues that flow into the music industry. Second, it would compensate recording artists, who are under-protected in the current regime, and augment their incentives to create. Third, this model would monetize illegal music consumption, and would achieve this at a relatively low cost and without harming law-enforcement efforts. Fourth, and finally, the model would potentially change the power balance within the music industry in favor of artists instead of intermediaries.